Genomic context-dependent histone H3K36 methylation by three Drosophila methyltransferases and implications for dedicated chromatin readers - Jayakrishnan, Muhunden; Havlová, Magdalena; Veverka, Václav; Regnard, Catherine; Becker, Peter B (Nucleic acids research, 2025)
Methylation of histone H3 at lysine 36 (H3K36me3) marks active chromatin. The mark is interpreted by epigenetic readers that assist transcription and safeguard chromatin fiber integrity. In Drosophila, the chromodomain protein MSL3 binds H3K36me3 at X-chromosomal genes to implement dosage compensation. The PWWP-domain protein JASPer recruits the JIL1 kinase to active chromatin on all chromosomes. Because depletion of K36me3 had variable, locus-specific effects on the interactions of those readers, we systematically studied K36 methylation in a defined cellular model. Contrasting prevailing models, we found that K36me1, K36me2, and K36me3 each contribute to distinct chromatin states. Monitoring the changing K36 methylation landscape upon depletion of the three methyltransferases Set2, NSD, and Ash1 revealed local, context-specific methylation signatures. Each methyltransferase governs K36 methylation in dedicated genomic regions, with minor overlaps. Set2 catalyzes K36me3 predominantly at transcriptionally active euchromatin. NSD places K36me2/3 at defined loci within pericentric heterochromatin and on weakly transcribed euchromatic genes. Ash1 deposits K36me1 at putative enhancers. The mapping of MSL3 and JASPer suggested that they bind K36me2 in addition to K36me3, which was confirmed by direct affinity measurement. This dual specificity attracts the readers to a broader range of chromosomal locations and increases the robustness of their actions.
Keywords: metylace; DNA vazebné proteiny; Animals; Euchromatin; Lysine; lysin; histonlysin-N-methyltransferasa; transkripční faktory; Chromatin; euchromatin; heterochromatin; Heterochromatin; Transcription Factors; Protein Serine-Threonine Kinases; Methylation; Histone-Lysine N-Methyltransferase; Drosophila Proteins; chromatin; Drosophila melanogaster; DNA-Binding Proteins; proteiny Drosophily; histony; Histones; zvířata; protein-serin-threoninkinasy